Metaphors of flood disaster in Malaysian media: a cognitive metaphor perspective - Chong, S. T.; Ng, Y. J.; Karthikeyan, J.; Mohd. Kasim, Zalina (Primrose Hall Publishing Group, 2020)
This paper examines the metaphors used in media discourses related to flood disasters in Malaysia from 2014-2017 in various media discourses. Flood disaster has become a serious challenge and problem to all Malaysians. The theoretical framework used in this study is Lakoff’s Conceptual Metaphor Theory. The methodological framework is Charteris-Black’s method of analysing metaphors in media discourses. The materials used in this study are news articles from various public media in Malaysia. This paper argues that the media used metaphors to reduce the anger and impact of the citizens. Besides, the metaphors are used to ingrain the idea that flood is not man-made but the wrath of Mother Nature. The conclusion of this article is to present the way media portrays flood disaster to the public. The paper contributes to the gap of the argument in authentic reporting about flood disasters in Malaysian media.